BMI is an independent prognostic factor for late outcome in patients diagnosed with early breast cancer: A landmark survival analysis. (October 2019) - Vernaci, Grazia; Dieci, Maria Vittoria; Manfrin, Silvia; Mantiero, Mara; Falci, Cristina; Faggioni, Giovanni; Mioranza, Eleonora; Menichetti, Alice; Tasca, Giulia; Griguolo, Gaia; Miglietta, Federica; Di Liso, Elisabetta; et al.
Highlights: BMI negatively affects breast cancer survival. Higher BMI is associated with older age, post-menopausal status and advanced stages. Obese patients experience a poorer iDFS and OS at 15 years. Obesity is an independent prognostic factor for late outcome. The distribution of late events varies significantly according to BMI class.